DEGRADASI LINGKUNGAN DAN PEMBANGUNAN BERKELANJUTAN: EFEKTIVITAS KERJA SAMA UNEP DAN ASEAN DALAM MENGATASI PERMASALAHAN LINGKUNGAN HIDUP DI ASIA TENGGARA - Wijaya, Bagaskara Sagita; Feni Fitriani Putri Rozi; Sarach Respilia Sukma; Kamilia Nadirah (Indonesian Association for International Relations, 2024)
Environmental problems, classified as non-traditional security issues, have become essential problems for countries and regions worldwide. Environmental degradation, such as Haze Pollution, and conservation efforts through sustainable development are the focus of global environmental problems because they cross national borders and require international cooperation. One of region with environmental issues that starting to cooperate to tackle environmental problems are ASEAN. This article shows that cooperation between UNEP (United Nations Environment Program) and ASEAN countries is the key to facing cross-border environmental challenges, increasing public awareness, building capacity, and formulating effective environmental policies. The research method used is qualitative, with a literature and phenomenology approach, using basic arguments from Green Theory to analyze the problem. The research results state that this cooperation protects the natural environment, encourages sustainable development, and contributes to the global agenda for environmental conservation. Environmental cooperation based on an eco-centrism view will have a massive impact on maintaining ecological sustainability. To create Sustainable Development in the Green Environment aspect by making various simple efforts to bring significant changes to the world, especially the ASEAN community